Improving Student Learning Outcomes Through The Implementation of Storytelling Cooperative Learning Models - Istiqamah Hafid; Verawati Verawati; M. Fatchurahman; Siti Juhairiah (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Educational philosophy subject is one of mandatory subject that should be taken by student in the first semester of Primary Teacher Education Program in University of Muhammadiyah Palangkaraya. In fact, many students complained about difficulties in understanding the content of this subject. Cooperative learning by using storytelling method is one of the methodologies that can be used in teaching learning process. There are no previous research results that examine the cooperative learning model using the storytelling method, so researchers are interested in researching the implementation of the cooperative learning model using the storytelling method in improving student learning outcomes. This research uses the Classroom Action Research (CAR) method which focuses on efforts to improve student learning outcomes in educational philosophy subject. This research consist of 2 cycles, In cycle 1 students have not been able to reach the criteria for completion that has been determined. The class average score is 70, with learning completion was 62% or as many as 26 students from total 42 students. Therefore, cycle II has to be taken by the researcher, and as the result of cycle II the students has achieved the criteria for completion that were previously determined, with average score obtained was 85, 85% of students completed their studies (36 students from total 42 students).